2004
DOI: 10.1093/nar/gkh561
|View full text |Cite
|
Sign up to set email alerts
|

Multiple protein/protein and protein/RNA interactions suggest roles for yeast DNA/RNA helicase Sen1p in transcription, transcription-coupled DNA repair and RNA processing

Abstract: Sen1p in Saccharomyces cerevisiae is a Type I DNA/RNA helicase. Mutations in the helicase domain perturb accumulation of diverse RNA classes, and Sen1p has been implicated in 3' end formation of non-coding RNAs. Using a combination of global and candidate-specific two hybrid screens, eight proteins were identified that interact with Sen1p. Interactions with three of the proteins were analyzed further: Rpo21p(Rpb1p), a subunit of RNA polymerase II, Rad2p, a deoxyribonuclease required in DNA repair, and Rnt1p (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
147
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(151 citation statements)
references
References 41 publications
2
147
2
Order By: Relevance
“…Sen1 has a specific function in termination of non‐coding transcription in yeast cells (Steinmetz et al , 2006) and the endogenous full‐length protein can indeed recapitulate transcription termination in reconstituted in vitro assays (Porrua & Libri, 2013). The most characteristic feature of Sen1 is the presence of a large N‐terminal domain, which is important for Sen1 function in vivo (Ursic et al , 2004). However, we have found that the helicase core of Sen1 retains all the properties that are necessary for transcription termination in vitro (Fig 1).…”
Section: Resultsmentioning
confidence: 99%
“…Sen1 has a specific function in termination of non‐coding transcription in yeast cells (Steinmetz et al , 2006) and the endogenous full‐length protein can indeed recapitulate transcription termination in reconstituted in vitro assays (Porrua & Libri, 2013). The most characteristic feature of Sen1 is the presence of a large N‐terminal domain, which is important for Sen1 function in vivo (Ursic et al , 2004). However, we have found that the helicase core of Sen1 retains all the properties that are necessary for transcription termination in vitro (Fig 1).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, even though Sen1 was previously detected at snoRNAs genes (Kim et al 2006), readthrough at noncoding and some coding genes in a SEN1 mutant strain supports Sen1 involvement in termination of both class of RNAs (Steinmetz et al 2006b). Sen1 is a large, low-abundance nuclear protein that interacts with the CTD (Ursic et al 2004) and is implicated in processing of a variety of noncoding RNAs (Winey and Culbertson 1988;Ursic et al 1995).…”
Section: Rat1/xrn2: the Transcription Termination Torpedomentioning
confidence: 99%
“…Nrd1 (nuclear pre-mRNA down-regulation) is an essential nuclear RNA-binding protein that directs termination of snoRNA and some mRNA transcripts, in association with an interacting protein, the helicase Sen1 (Steinmetz and Brow 1996;Steinmetz et al 2001;Ursic et al 2004;Vasiljeva and Buratowski 2006). Nrd1 contains a CID (Meinhart and Cramer 2004;Meinhart et al 2005) that interacts with CTD phosphorylated at Ser5 (Conrad et al 2000;Gudipati et al 2008;Vasiljeva et al 2008a).…”
Section: The Nrd1 Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…14 AOA2 cells are defective in a protein (senataxin) homologous to a yeast protein involved in DNA repair and RNA processing. 16,29 Given the cellular characteristics described here for the patient, together with the overlapping clinical phenotype of this patient with other AOA syndromes, it seems likely that the defective gene in this case will also be associated with some aspect of DNA damage processing and signalling to apoptosis. However, no mutations were observed in APTX, SETX or ATM in the patient's cells.…”
Section: Discussionmentioning
confidence: 95%